Sosialiasi Stop Bullying, Edukasi Kebersihan dan Kreativitas di SD Negeri Lancong - Mahmud Basuki; Suib Umami Sitorus; Fajratul Rahmi; Cut Tiara Safitri; Liliana Febria; Rahmita Yanti; Yurisa Nurhijarah; Tegar Prayoga; M. Farhan; Iing Pamungkas (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
This community service activity is part of the Regular Community Service Program (KKN) held in Lancong Village, Sungai Mas District, West Aceh Regency. The focus of this activity is to increase elementary school students' awareness of the dangers of bullying, strengthen clean and healthy living behaviors (PHBS), and develop creativity in the learning process. The background of this activity is based on the still low understanding of some students about the negative impacts of bullying, lack of habits of maintaining personal hygiene, and limited channels for expressing creative ideas in schools. The activity was carried out at Lancong Public Elementary School involving students in grades 4 to 6 through an interactive educational approach. The methods used included informative presentations, educational games, group discussions, and creative practice in the form of making thematic posters. The session on bullying was aimed at providing an understanding of the forms of bullying, its impact on victims and the school environment, as well as prevention and handling strategies. PHBS material was delivered through demonstrations of how to wash hands properly, maintain a clean classroom environment, and the implementation of a healthy lifestyle every day. In the creativity development section, students were invited to express anti-bullying and PHBS messages through posters that were then presented in front of their peers. The results of the activity showed an increase in students' understanding of the importance of mutual respect, avoiding bullying, and practicing healthy lifestyles. Furthermore, students' skills in expressing ideas creatively also developed, as seen from the enthusiasm and quality of the posters produced. This program has had a positive impact on shaping positive attitudes and habits in the school environment, while also serving as a model for educational activities that can be implemented in other schools. Thus, this activity contributes to the holistic development of students' character, encompassing social, health, and creativity aspects.